Novel pH-sensitive polysialic acid based polymeric micelles for triggered intracellular release of hydrophobic drug. (30th March 2016) - Zhang, Wuxia; Dong, Dongqi; Li, Peng; Wang, Dongdong; Mu, Haibo; Niu, Hong; Duan, Jinyou
Highlights: A novel intracellular pH-sensitive amphiphilic copolymer PSAU was synthesized. PTX-loaded-PSAU exhibited well-defined spherical shape and particle size. The drug-loading was 4.5% with an entrapment efficiency of 67.5%. PTX-loaded-PSAU micelles could efficiently release PTX in tumor cells. Abstract: Polysialic acid (PSA), a non-immunogenic and biodegradable natural polymer, is prone to hydrolysis under endo-lysosomal pH conditions. Here, we synthesized an intracellular pH-sensitive polysialic acid-ursolic acid conjugate by a condensation reaction. To further test the drug loading capability, we prepared paclitaxel-loaded polysialic acid-based amphiphilic copolymer micelle (PTX-loaded-PSAU) by a nanoprecipitation method. Results showed PTX-loaded-PSAU exhibited well-defined spherical shape and homogeneous distribution. The drug-loading was 4.5% with an entrapment efficiency of 67.5%. PTX released from PTX-loaded-PSAU was 15% and 42% in 72 h under simulated physiological condition (pH 7.4) and mild acidic conditions (pH 5.0), respectively. In addition, In vitro cytotoxicity assay showed that PTX-loaded-PSAU retained anti-tumor (SGC-7901) activity with a cell viability of 53.8% following 72 h incubation, indicating PTX-loaded-PSAU could efficiently release PTX into the tumor cells. These results indicated that the pH-responsive biodegradable PTX-loaded-PSAU possess superior extracellular stability and intracellular drug release ability.